Neuro-brucellosis. Report of 8 cases. - Dias, M S (1995)
Brucellosis is an endemic disease in Portugal. There was an increase in incidence in 1994. Neurobrucellosis (NB), although only occurring in 5 to 10% of cases of cases of chronic infection, has heterogeneous forms of presentation which makes differential diagnosis difficult. By reviewing four years of in-patient clinical files in the neurology Ward of St. António dos Capuchos Hospital, the authors study the clinical features, complementary tests, therapy and evolution of differential diagnosis of eight patients with neurobrucellosis.